South China Sea Dispute: What Alternative Solutions Can be Offered to the International Community? - Darajati, Muhammad Rafi; Sudagung, Adityo Darmawan (Padjadjaran Journal of International Law, 2023)
As the busiest shipping route with a high value of resources under the sea, the South China Sea dispute is one of the unresolved problems in recent world affairs. Claimant states keep on defending their claim over the territory. Several critical factors of the disputed areas, such as the international trade perspective, natural resources aspects, and the security value, did affect the behaviour of such states. A lot of alternatives and means have been done to solve the case until the decision of PCA on the Philippine claim over China’s nine-dash line. Non-compliance response of China did raise another tension on the issue and complicated the resolution. We offered more alternatives to the international community to act, which combined peace-oriented bilateral and multilateral diplomacy and cooperation to force all claimants to agree on their maritime boundary, seeking mediation from states that can be trustworthy, international sanctions might be an option - but with a highly calculated decision, and stressing the compliance with legal action to gain trust from other parties. to support the diplomacy that takes place in the process.